Efficient dual-scale flow simulation for Resin Transfer Molding process based on domains skeletonization. (February 2023) - Bancora, S.; Binetruy, C.; Advani, S.; Comas-Cardona, S.; Leygue, A.
Abstract: In the Resin Transfer Molding (RTM) process, a polymeric resin is injected inside a dry preform to fill the gaps around and inside the fiber tows. Simulating this process at the scale of the tows is challenging because of the computational cost associated to solving a three-dimensional dual-scale flow problem. In this work, a novel Dual-Scale Skeleton model (DSS) is introduced, capable of solving a dual-scale flow problem at an affordable computational cost. The three-dimensional geometry of a multi-layer layup, consisting of inter-tow channels and permeable tows, is replaced by a skeletonized representation of the original subdomains. Dual-scale flow is modeled using a Reynolds–Darcy finite elements formulation. The model is validated numerically and its application is demonstrated over a few test cases. The adoption of the DSS model allows one to simulate complex dual-scale flow problems over large domains at a reduced computational cost when compared to full 3D solutions.